Adoption of telepharmacy among pharmacists, physicians, and nurses at Hawassa City Public Hospitals, Ethiopia. - Jenberu Mekurianew Kelkay; Henok Dessie Wubneh; Henok Molla Beri; Abel Melaku Tefera; Rediet Abebe Molla; Addisu Alem Negatu (PLOS Digital Health)
Pharmaceutical care in the majority of developing countries is hindered by a lack of techniques, limitations in mobility, and a shortage of staff to provide patient care. However, there is no evidence that professionals intend to use telepharmacy in patient care. To fill this gap, this study was designed to examine whether pharmacists, physicians, and nursing professionals intend to use telepharamcy in their care practice.A cross-sectional investigation was carried out from November 29 to December 30, 2023. A study was conducted at all Hawassa public hospitals. A total of 592 Pharmacists, Physicians, and nurses participated. Simple random sampling and proportional allocation were utilized. A structured self-administered questionnaire was used, and a 5% pretest was administered. The data were entered into Epi Data 4.6 and exported to SPSS 26. The AMOS 23 SEM was also used to describe and assess the degree and significance of the relationships between variables.51.4% (304/592) (95% CI, 47.2-55.4) of the participants intended to use telepharmacy. Performance expectancy (β = 0.23, p-value <0.05), social influence (β = 0.295, p-value <0.05), and digital literacy (β = 0.309, p-value <0.001) had positive relationships with the intention to use telepharmacy. Age and gender were also moderators of performance expectancy in telepharmacy.Overall, Pharmacists', Physicians', and nurses' intentions to use telepharamcy were found to be promising for the future. Performance expectancy, social influence, and digital literacy had a significantly positive influence on the intention to use telepharamcy. Digital literacy had a more significant prediction power than others. The results could be useful in terms of designing emerging systems and understanding users' computer skills.